EROI of the Ukrainian coal - Cherevatskyi, D.; Atabyekov, O. (Економічний вісник Донбасу, 2017)
The concept of EROI (energy return on investment) has become a commonly used synonym for energy efficiency, an alternative to traditional economic evaluation. This work was carried out with the goal of drawing up methodology for determining the significance of the main factors affecting the dynamics of the energy efficiency of Ukrainian coal and assessing the real situation in the coal branch. The coal mining enterprise is represented in the form of distributed flows of coal, symbolizing the energy resources: actually spent at the mine; sent to the metallurgical (by-product) plant; to the power station; spent in the everyday life of all technologically related enterprises personnel, etc. Поняття EROI (energy return on investment) стало загальновживаним синонімом енергетичної рентабельності, певною альтернативою традиційної економічної оцінки. Дослідження виконано з метою складання методичних положень щодо встановлення значимості основних чинників, що впливають на динаміку показників енергетичної ефективності вугілля українських шахт, і оцінки реальної ситуації в галузі. Вугледобувне підприємство представлено як розподілені потоки вугілля, які символізують енергетичні ресурси: що витрачаються по шахті; відправляються на металургійний (коксохімічний) завод; на електростанцію; споживаються в побуті персоналом всіх технологічно пов'язаних підприємств тощо. Понятие EROI (energy return on investment) стало общеупотребительным синонимом энергетической рентабельности, определенной альтернативой традиционной экономической оценки. Работа выполнена с целью составления методических положений по установлению значимости основных факторов, влияющих на динамику изменения показателей энергетической эффективности угля украинских шахт, и оценки реальной ситуации в отрасли. Угледобывающее предприятие представлено в виде распределенных потоков угля, символизирующих энергетические ресурсы: собственно расходуемые на шахте; отправляемые на металлургический (коксохимический) завод; на электростанцию; расходуемые в быту персоналом всех технологически связанных предприятий и т.п.